Bibliometric Analysis of Learning Styles Research in Higher Education: Trends and Insights from 1973 to 2024 - Dinnah Raihanah (Scientia Publica Media, 2025)
Identifying students’ learning styles is essential for enhancing the quality of education. This study aims to comprehensively understand the publication trends and conceptual, intellectual, and social structures within the topic of learning styles in higher education. The literature data was sourced from the Scopus database, covering the period from 1973 to 2024, and analyzed using bibliometric methods. This process began with an initial identification of 3,779 articles, which were then filtered according to specific criteria, resulting in 2,190 selected articles for in-depth analysis. The findings of this study reveal critical themes within the topic of learning styles and provide statistical insights through tables, graphs, and maps. This research also examines keywords and citations based on scientific publications. The results indicate that learning styles are closely linked with learning outcomes, learning objects, and students’ psychological aspects. A notable increase in publications began around 2001, reaching a peak in 2022 with 131 articles. Analysis reveals the three authors with the greatest publication output in this domain are Brown T., Van Petegem P., and Vermunt JD. The analysis identifies BMC Medical Education as the leading journal publishing research on learning styles in higher education, followed by Medical Teacher and Nurse Education Today. Based on bibliometric analysis, the most cited article was authored by Kolb A.Y. in 2005. The countries with the greatest publication output are the United States and the United Kingdom. The relevant keywords include “human,” “learning,” “female,” “article,” “male,” “humans,” “learning styles,” “teaching,” “adult,” and “education.” This information is expected to help researchers further develop, explore, and uncover additional dimensions, themes, ideas, and research trends related to the topic of learning styles in higher education.